A generalized method of zone construction for plane zone plate antennas - Dey K.K.; Khastgir P. (My University, 2025)
A general mothod for the zone construction of a microwave piane zone plate antenna is presented on the basis of the Fresnel-Huygcn diffraction theory. It is found that the classical mode of zone plate construction, on the basis of path differences, fits in admirably in this more general framework. The method is also applicable to the case of spherical zone plates. © 1974 Taylor and Francis Group, LLC.